Clinical Manifestations and Molecular Backgrounds of Parkinson's Disease Regarding Genes Identified From Familial and Population Studies - Nishioka, Kenya; Imai, Yuzuru; Yoshino, Hiroyo; Li, Yuanzhe; Funayama, Manabu; Hattori, Nobutaka (Frontiers in Neurology, 2022)
Over the past 20 years, numerous robust analyses have identified over 20 genes related to familial Parkinson's disease (PD), thereby uncovering its molecular underpinnings and giving rise to more sophisticated approaches to investigate its pathogenesis. α-Synuclein is a major component of Lewy bodies (LBs) and behaves in a prion-like manner. The discovery of α-Synuclein enables an in-depth understanding of the pathology behind the generation of LBs and dopaminergic neuronal loss. Understanding the pathophysiological roles of genes identified from PD families is uncovering the molecular mechanisms, such as defects in dopamine biosynthesis and metabolism, excessive oxidative stress, dysfunction of mitochondrial maintenance, and abnormalities in the autophagy–lysosome pathway, involved in PD pathogenesis. This review summarizes the current knowledge on familial PD genes detected by both single-gene analyses obeying the Mendelian inheritance and meta-analyses of genome-wide association studies (GWAS) from genome libraries of PD. Studying the functional role of these genes might potentially elucidate the pathological mechanisms underlying familial PD and sporadic PD and stimulate future investigations to decipher the common pathways between the diseases.